Control of Electric Drive with Predicting Model - N. N. Micheev; E. P. Ratkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2006)
The electric drive system with a predicting model makes it possible to ensure control in accordance with a selected optimum criterion at the given limitations on coordinates under conditions of changeable parameters and external actions on an object to be controlled within permissible boundaries. The proposed control system presupposes to build a predicting model on the basis of an optimized object in accordance with an optimum criterion. While constructing the model it is necessary preliminary to distinguish a mathematical description of three higher external coordinates.The object model acquires prediction properties after setting scale time coefficients in it. The proposed predicting model permits to exclude immediate rapid time calculations of a control value.